WETLAND AND BIOCULTURAL HERITAGE REGENERATION THROUGH THEMATIC ECOLOGICAL TOURISM PRACTICE: THE CASE OF PATAN SUB-DISTRICT, KHUN TAN DISTRICT, CHIANG RAI, THAILAND - Siripen YIAMJANYA; Kannapat KANKAEW; Bussaba SITIKARN; Parinya NAKPATHOM; Ali Mohsin Salim Ba AWAIN; Teerarat JABJAINAI (Geo Journal of Tourism and Geosites)
The tourism managed and operated by local communities has evidently been a significant phenomenon in the 21st century, and therefore it is one of the challenging units in the tourism value chain. This study investigates the initiative of community ecological tourism and proposes a framework of ecological tourism development. The inductive approach utilizes field survey, in-depth interviews, participatory observation, focus group discussion with key tourism partners. The concept of public private partnership (PPP) was applied. The analytic hierarchy process (AHP) was employed to rank the criteria for ecological tourism development. The structural equation modelling (SEM), as a quantitative approach, was used to foster the factors collected from the focus group. There are six criteria identified for sustainable ecological tourism development including: environmental, economic, sociocultural, visitor experiences, infrastructure and logistics, and sustainability. Other six factors enhance ecological tourism development namely: budget, knowledge, technological system, participation, community factors, and social factors. Stakeholders highlight environment and community participation for sustainable development. Still, the local residents lack knowledge on tourism management. Based on the findings, the sustainable ecological tourism development framework for Patan was constructed. Future success factors that should be essentially developed involve inventory of local data that will be useful for establishing identity and meaning making, local individuals’ learning and understanding of their local knowledge, training and tourism interpretation and narratives for story-telling of its cultural landscape.